2015
DOI: 10.1016/bs.pmbts.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Mechanisms Underlying Ocular Growth and Myopia

Abstract: In the regulation of ocular growth, scleral events critically determine eye size and thus the refractive status of the eye. Increased scleral matrix remodeling can lead to exaggerated eye growth causing myopia and additionally increased risk of ocular pathological complications. Thus, therapies targeting these changes in sclera hold potential to limit such complications since sclera represents a relatively safe and accessible drug target. Understanding the scleral molecular mechanisms underlying ocular growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…27 Finally, a reduction in amount of collagen in the extracellular matrix of the sclera can accelerate axial elongation and promote the progression of myopia. [61][62][63] In summary, we found that the changes in ChT and ChBP in guinea pig models of myopia are similar to those in human myopia. The choroidal circulation is critical for meeting the oxygen demands of the retina and sclera, and decreases in ChBP can lead to a relatively hypoxic environment, which in turn could induce axial elongation and myopia progression.…”
Section: Pathologic Effects Of Decreased Chbp On the Retina And Sclersupporting
confidence: 67%
“…27 Finally, a reduction in amount of collagen in the extracellular matrix of the sclera can accelerate axial elongation and promote the progression of myopia. [61][62][63] In summary, we found that the changes in ChT and ChBP in guinea pig models of myopia are similar to those in human myopia. The choroidal circulation is critical for meeting the oxygen demands of the retina and sclera, and decreases in ChBP can lead to a relatively hypoxic environment, which in turn could induce axial elongation and myopia progression.…”
Section: Pathologic Effects Of Decreased Chbp On the Retina And Sclersupporting
confidence: 67%
“…For example, the exact ocular site of action of atropine's inhibitory effect on myopia progression remains unresolved, with the sclera, choroid, and retina among possibilities; underlying cellular and pharmacological mechanisms also remain unresolved. 239,240 Until consensus is reached on the ocular tissue to be targeted, advances in drug delivery cannot been fully exploited to optimize formulations. Additional studies are also needed to establish optimal atropine dosing and treatment regimens, including how long treatment should be continued, when/how it should be stopped, and the possibility of ''prescribing'' short drug holidays to prevent tolerance with higher concentrations.…”
Section: Pharmacological Control Of Myopiamentioning
confidence: 99%
“…Scleral thinning has been reported in high axial myopia and pathological myopia [21][22][23]. e thickness of the posterior sclera of pathological myopic eyes has been reduced up to 31% compared to the sclera in nonmyopic eyes [24]. During the development of myopia, several structural changes occur such as an increase in collagen degrading enzymes and a reduction of the scleral component of collagen [18,25].…”
Section: Discussionmentioning
confidence: 99%